A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

The impacts of IFRS 16 on airlines - Ribeiro, José; Ribeiro, Francisco; Ribeiro, Fernando (Accounting and Management Review | Revista de Contabilidade e Gestão, 2023)
This study addresses the effects of the adoption of IFRS 16 on the passenger air transport sector. With practical effects for financial years beginning on or after 1 January 2019, IFRS 16 established the standardisation of a single accounting modelfor all leases, whether operating or financial. With this new adoption, IFRS 16 aims to increase the transparency and quality of the information that is presented in the financial statements for the most diverse stakeholders. This study aimed to assess the effects of adopting this new international standard in a specific sector and to identify whether the changes in some of the financial indicators are felt in the same way by all companies, this being the main focus of this study. Based on a sample of 12 airlines from various countries in Europe and South America, the financial indicators were interpreted by analysing the reports and accounts before and after the application of IFRS 16. The main conclusions obtained are: i) the adoption of IFRS 16 led to an increase in assets, liabilities and EBITDA, however in different proportions for each of these items; ii) companies with negative equity and, therefore, with greater risks of bankruptcy or greater information asymmetry, tend to resort more to leasing as a way of financing their assets; iii) the financial autonomy and solvency ratios showed significant variations for companies that resort more to operating leasing.
Keywords: Airline industry; Finance leases; IFRS 16; Information asymmetry.

Prospects for an African continental model multilateral tax agreement for the co-ordination of cross-border corporate tax challenges - Fehun Aren, Marie-Louise (University of Pretoria, 2023)
This study explores the creation of an African Continental Model Multilateral Tax Agreement (MMTA) to address the limitations of current bilateral tax treaties and enhance existing African Regional Economic Community (REC) frameworks for more effective taxation of cross-border business profits. Focusing on critical international taxation framework issues such as taxing rights allocation, Permanent Establishment criteria, and tax dispute resolution, it compares African REC MMTA provisions with those in non-African agreements to identify key weaknesses and propose improvements. The proposed MMTA aims to ensure equitable taxing rights, update nexus rules to capture both physical and digital businesses, and provide robust dispute resolution mechanisms to foster investment. It advocates for harmonized tax policies and tax agreements across African RECs to minimize tax competition, promote intra-African trade, and support regional economic integration under the African Continental Free Trade Area (AfCFTA). By aligning with the Abuja Treaty’s objectives, the framework seeks to enhance revenue mobilization and sustainable economic development in Africa. This research provides a roadmap for creating a tailored multilateral tax treaty that balances diverse regional interests, addressing Africa’s development financing needs while promoting cross-border taxation efficiency.
Keywords: AfCFTA; African Continental Free Trade Area; Continental model; International taxation frameworks; Multilateral tax agreement; Revenue mobilisation; Tax treaties

Earnings Management and Default Risk - Nguyen, Loan (Victoria University of Wellington, 2023)
This thesis comprehensively investigates the relationship between default risk (DR) and earnings management (EM) by addressing inconsistencies in prior research regarding the level and direction of EM in response to varying levels of DR. The thesis extends beyond severe financial distress to include firms with low and medium levels of distress. It examines the non-monotonic relationship between DR and EM, considering accrual earnings management (AEM), real earnings management (REM), and total earnings management (TEM). The thesis also examines the impact of DR on the relative use of REM versus AEM. The moderating effect of the global financial crisis (GFC) on the relationship between DR and EM is also explored.Using a sample of 29,228 firm-year observations from 4,514 US-listed firms during 2001-2019, the study employs both the traditional two-step and the more recent one-step approaches to identify EM. Sensitivity analysis is conducted, including and excluding mining firms.The findings reveal a non-monotonic relationship between DR and REM, with a concave pattern observed for all measures of REM. Initially, REM increases as DR rises, but it subsequently declines with further increases in DR. AEM, on the other hand, shows a convex or monotonically decreasing relationship with DR, although statistical significance is not consistently observed. The results for TEM align with those of REM, indicating the dominance of REM in TEM. These findings remain consistent when excluding mining industry observations and using different measures for EM and DR.The implications of these findings are significant for managers, firms, regulators, lenders, investors, and other stakeholders. The non-monotonic relationship between DR and REM offers insights for decision-making and determining appropriate levels of EM during varying levels of DR. Regulators can utilise this relationship to identify potential risk areas and develop effective regulations. Lenders can assess financial statements more vigilantly, and investors can make more accurate risk assessments and informed investment decisions. The robustness of the results and the inclusion of different EM measures provide valuable insights to auditors, analysts, and government professionals, enhancing their understanding of the complexities and risks associated with EM during varying levels of DR.The study also uncovers that the relative use of AEM and REM is complimentary, but the impact of DR dampens the increase in REM for a given increase in AEM. This result holds across primary and alternative measures of DR and is of significant interest to managers, firms, regulators, and other stakeholders. It provides insights into the interplay between AEM and REM, enabling informed decisions about EM strategies under different levels of DR. Regulators can leverage this information to identify potential risk areas and develop effective regulations to mitigate EM practices that could lead to financial instability. Lenders and investors benefit from understanding how DR affects the relative use of AEM and REM, enabling them to assess financial statements and manage investment risk more accurately. The study’s findings contribute to a deeper understanding of EM dynamics and have practical implications for various stakeholders in the financial ecosystem.Furthermore, the thesis investigates EM measures during the GFC and the moderating effect of the GFC on the relationship between DR and EM. The inclusion of REM and TEM, in addition to AEM, provides a comprehensive understanding of how firms managed their earnings during the GFC, offering insights into the effectiveness and implications of different EM strategies during a financial crisis. It confirms the decline of AEM during the GFC, reinforcing existing knowledge about the impact of the crisis on EM practices. Additionally, it identifies a negative impact of the GFC on REM and TEM, providing further evidence of the challenges and changes in EM strategies faced by firms during the economic crisis. The study also finds an insignificant moderating effect of the GFC on the relationship between DR and REM, as well as DR and TEM, shedding light on EM variation across different economic stages.Overall, this thesis contributes to the EM literature by examining the non-monotonic impact of DR on EM measures, comparing different approaches to identify EM, exploring the moderating effect of DR on the relative use of AEM and REM, and investigating EM measures during the GFC. The insights from this research assist managers in decision-making, firms in adapting financial management strategies, regulators in developing policies, lenders in risk assessment, and investors in understanding the complexities and risks associated with EM. The findings have practical implications for various stakeholders in the financial realm, guiding decision-making, regulatory efforts, risk assessment, and investment strategies.Keywords: earnings management, accruals earnings management, real earnings management, default risk, global financial crisis, one-step approach, two-step approach.

Corporate Finance, Governance, and Social Responsibility - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers 27 papers published in the Special Issue entitled Corporate Finance, Governance, and Social Responsibility, which examines several topics related to corporate finance, financial modeling, corporate governance, and corporate social responsibility. Corporate finance-related articles (Anton and Afloarei Nucu, 2021; Bae et al., 2023; Kedzior et al., 2020; Lts and Lukason, 2022; Miglo, 2020; Mihail et al., 2021; Mota and Moreira, 2023; Tsolas, 2021; Tudose et al., 2021; and Wen et al., 2021) focus on the drivers of the capital structure and firm performance, the effect of working capital management on profitability, and the link between derivative use and profitability. Regarding financial modeling, stock market volatility was explored during COVID-19 (Gherghina et al., 2021). Corporate governance studies (Aluchna and Kuszewski, 2020; Ararat et al., 2021; Ding and Chea, 2021; Kjrland et al., 2020; Loureno et al., 2021; Lukason and Camacho-Miano, 2020; Maier and Yurtoglu, 2022; Mihail and Dumitrescu, 2021; Mihail et al., 2022; Mihail and Micu, 2021; and Pourmansouri et al., 2022) examine the effect of corporate governance compliance practices, board attributes, or employee stock option plans on bankruptcy risk, performance, firm value, or earnings management. Regarding CSR (Bozos et al., 2022; Rossi et al., 2021; Saeed and Sroufe, 2021; Singh and Hong, 2023; and Tseng and Shih, 2022), the research focuses on how CSR affects financial performance, risk management, or analyst profits estimates.
Keywords: CSR; Corporate Finance; Financial performance

Artificial Intelligence: Challenges and Opportunities for the Accounting Profession in Nigeria - Nkwede, Maria; Aniuga, Chukwuma (African Journal of Politics and Administrative Studies, 2023)
Artificial intelligence with its fifth industrial revolution is fast griping the African continent. The emergence and adoption of artificial intelligence applications and systems is fast becoming a normal trend in emerging markets landscape across Africa. This paper is borne out of the need to identify challenges that professional grapple with in their quest to surmount the challenges posed by the realities of artificial intelligence applications in Africa. The study adopted the thematic style in presenting the challenges as well as the prospects of artificial intelligence applications for the accounting professional in emerging market. Some of the challenges of artificial intelligence application identified in this study include: complex algorithms, reduced investment, and software failure, lack of political will and limitations amongst others. On the other hand, opportunities of artificial intelligence in emerging market include transportation automation, technological cyborgs and robotic companions amongst others. From the findings, accounting professional are advised to strive harder in order to beat competition by delivering quality services to her clients through harnessing opportunities for rebranding, reengineering and radically improving the business and investment decisions which is the ultimate purpose of the profession. More so, they are encouraged to develop a novel set of proficiency revolving around data in the profession
Keywords: AI; Accounting Profession; Artificial Intelligence; Challenges; Fifth Industrial Revolution; Inteligência artificial; Intelligence Artificielle; Opportunities

Saudi Banks Level of Compliance with Accounting Standards of Accounting and Auditing Organization for Islamic Financial Institutions - A. Al-Bogami, S. (Information Sciences Letters, 2023)

The Relation between Corporate Governance, Risk Management and Financial Performance: Theoretical and Analytics Framework - Ayoob Mohammed Hassan, Noora; Din, Badariah binti Haji; Senasi, Vally (Information Sciences Letters, 2023)
The paper aims to review the relation between Corporate Governance, Risk Management and Performance. We reviewed these variables and develop a Theoretical and Analytics framework. First introduction (study background, Problem Statement, Research Objectives and research questions). Second literature review (A) financial performance such as ROA, ROE, EPS and Tobin’s Q, (B) Corporate Governance as Board of Directors, Board Composition, CEO Duality and Board Size (C) Risk Management. Third, we discussed Underpinning Theories such as, Agency Theory and Institutional Theory. Fourth, we developed a Theoretical Framework where we illustrated (A) Corporate Governance and Financial Performance, (B) Risk Management and Financial Performance (C) Compliance with Accounting Standards and Financial Performance. Finally, we developed a comprehensive reviewing based on above variables.
Keywords: Corporate governance; Performance; Risk Management

Influence of Training, Experience, and Expertise on Quality of Financial Reporting in Dubai – Mediation of Adoption of International Public Sector Accounting Standards - IPSAS - El Haron, Esam O.; Haji Din, Badariah (Information Sciences Letters, 2023)

Accounting Choices During COVID 19 Pandemic: Does Corporate Strategy and Corporate Social Responsibility Matter? - T. Hassan, N. (Information Sciences Letters, 2023)
This study aims to understand the accounting effects of the Corona pandemic in more depth and clarity, where the study explores the accounting choices during the pandemic period and the impact of the firm's strategic orientation and its social responsibility performance on those choices. Using data from non-financial Saudi companies, the accounting choices divided into aggressive accounting strategy and conservative accounting strategy, and regression models used to examine the study hypotheses. The results of the study provide a clearer and in-depth vision about the nature of accounting practices during the pandemic and indicated that business strategy affects accounting choices, while corporate social responsibility does not affect. The results can imply useful information for the market regulators that help them in controlling and stabilizing the market, as well as for professional accounting organizations to help them issue guidelines for accounting work during crises.
Keywords: Accounting choices; CSR; Corporate Social Responsibility; Corporate strategy; Covid-19 pandemic; Saudi companies

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

Banking System Fragility in Nigeria: Hanging on the Precipice? - Kayode, Peter; Oluwole, Foluso (AAU Journal of Business and Law, 2023)
The health of a country’s banking system is a key determinant to the development of the country. A fragile banking system portends danger not only to the financial system but the entire economy. This study investigates the state of the Nigerian banking system in terms of stability or fragility from 1981 to 2020. We used the banking system fragility index (BSFI) proposed by Kibritçioğlu (2003) to analyze Nigerian banking industry aggregate data from three risk areas: credit, market and liquidity. We estimated that out of the 40 years examined, the banking system was fragile for 23 years given their BSFI less than 0 while it was not fragile for 17 years with BSFI = 0 or greater. We found that most of the years when the Nigerian banking system was fragile were periods of relaxed monetary policies, deregulation and credit expansion. Secondly, the years of banking system stability were when the county’s banking system was subjected to stiff regulation and consolidation. Given the number of years that the system was fragile, we observed that sustained economic growth and development requires that the banking system remain strong as long as possible, and that the Nigerian situation could not promote this important objective. We recommend that the financial regulatory authorities put in place more stringent policies as banks are more fragile during the deregulation of the banking industry.
Keywords: Banking system fragility; Precipice

The adoption of international financial reporting standards and foreign direct investment inflows: the moderating effect of the institutional environment in Africa - Simbi, Chipo (Rhodes University; Faculty of Commerce, Accounting, 2023)
Globalisation has created a need for an international accounting language to facilitate the smooth flow of trade across countries. In 2003, in an effort to establish a global financial reporting language, the International Accounting Standards Board (IASB) developed a single set of high-quality accounting principles known as the International Financial Reporting Standards (IFRS). Over the last decade, several African countries have adopted IFRS, and Africa has become the second-largest adopting continent after Europe. IFRS promotes improved quality of disclosure of accounting transactions, reduces information asymmetry between preparers and users of financial information, lowers the cost of investing, and breaks down information barriers to cross-border investment. Researchers suggest many benefits of IFRS adoption for macroeconomic indicators such as Foreign Direct Investment (FDI). The reduction in information acquisition and processing costs which translates into the reduction in investment costs, has been cited by most researchers. Researchers have argued, however, that the economic benefits of IFRS in Africa depend on the strength of the institutional environment. They also argue that the Western environment in which the IFRS was developed differs from the African environment. Thus, the universal approach of the IASB may not be appropriate due to the historical, social, economic and political context of African countries. The impact of the adoption of IFRS by African countries requires further examination, particularly as a weak institutional environment confronts many African countries. Three research questions are designed for this study; (1) Is there a significant change in FDI inflows for IFRS adopters in selected African countries after the adoption? (2) Is there a significant change in FDI inflows due to the institutional environment? (3) Does the institutional environment in IFRS-adopting countries moderate the effect of IFRS on FDI in selected African countries? The present study is underpinned by the new institutional theory, the information asymmetry theory, the eclectic theory and the signalling theory, each of which provide reasons why African countries have adopted IFRS. Nine hypotheses are developed, based on the research questions, and tested using the Systems General Method of Moments and the Difference-in-Difference method. The study uses data from 26 African countries, 15 adopting and 11 non-adopting countries, over the period 1996 - 2018. First, the study establishes that the adoption of IFRS positively and significantly affects FDI inflows into the selected sample of African countries. Second, the study concludes that legal enforcement, accounting and auditing standards enforcement, and language origin positively and significantly impact FDI inflows into these countries. Legal origin, however, has a positive but insignificant association with FDI inflows. Third, legal enforcement, historical ties, accounting and auditing enforcement and the quality of the institutional environment are found to moderate the effect of IFRS adoption on FDI inflows. These results indicate that IFRS is a crucial determinant of FDI inflows into African countries, but a supportive institutional environment is needed for African countries to attract FDI inflows after adoption. The results contribute to the accounting and finance literature on FDI into African countries, and may assist the investment community to assess the institutional risk associated with investing in IFRS adopting African countries.
Keywords: Accounting; Auditing; Difference in differences; FDI; Foreign direct investment; Generalized method of moments; IFRS adoption; Institutional infrastructure; International Financial Reporting Standards; Investments